1975
DOI: 10.1136/oem.32.2.119
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of concentrations of lead in human tissues.

Abstract: This postmortem study of lead concentrations in the tissues of 129 subjects is an extension to a report by Barry and Mossman (1970). Lead concentrations in bone greatly exceeded the concentrations in soft tissues and were highest in the dense bones. Bone lead concentrations increased with age in both sexes, more especially in male subjects and in dense bone, varying between mean values of 2-16 ppm in the ribs of children to over 50 ppm in the dense petrous temporal bones of elderly male adults. Male adults con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
217
1
19

Year Published

1977
1977
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(247 citation statements)
references
References 37 publications
10
217
1
19
Order By: Relevance
“…Most of the body Pb resides in the skeleton (Barry, 1975), which may offer protection to other tissues, but can also be a long-term source of Pb transfer to other tissues under conditions of bone resorption. For example, demineralization of bone in postmenopausal women can increase blood Pb (BPb) levels by 25% (Silbergeld et al, 1988), whereas the high bone turnover associated with pregnancy and lactation increases Pb levels in blood and breast milk (Gulson et al, 2003;Manton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the body Pb resides in the skeleton (Barry, 1975), which may offer protection to other tissues, but can also be a long-term source of Pb transfer to other tissues under conditions of bone resorption. For example, demineralization of bone in postmenopausal women can increase blood Pb (BPb) levels by 25% (Silbergeld et al, 1988), whereas the high bone turnover associated with pregnancy and lactation increases Pb levels in blood and breast milk (Gulson et al, 2003;Manton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The total for these two pools is about 3 mg. This is less than the total of 10-30 mg found in soft tissue at autopsy by Schioeder and Tipton (59) and the 9.3 mg mean in nonoccupationally exposed men, the 15.7 mg in men with occupational exposure, and the 6.2 mg in women, found by Barry (35).…”
Section: Environmental Health Perspectivesmentioning
confidence: 61%
“…However, its diagnostic value at the borderline of hazardous conditions is quite limited. It has been found that PbB is more a measure of very recent exposure (30)(31)(32)(33) than of total body burden, and most lead in the body is within the hard and soft tissues (33)(34)(35)(36). Below are some of the best data for "normal" concentrations of PbB.…”
Section: Terminologymentioning
confidence: 99%
See 2 more Smart Citations